Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Get the answers you need quickly and accurately from a dedicated community of experts on our Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

y = x + 2
5x - 4y = -3
Solving systems by equations


Sagot :

Answer: x = 5, y = 7

Step-by-step explanation:

1. First, put the variables together/rearrange:

y - x = 2 & 5x - 4y = -3

2. Cancel out variable x by multiply the first equation by 5:

5y - 5x = 10 & 5x - 4y = -3

3. Add equations:

y = 7

4. Then determine x by plugging y back into the first equation y = x + 2:

x = 5

Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.